Erratum to: Allergen immunotherapy for insect venom allergy: protocol for a systematic review. Issue 1 (15th September 2017) - Dhami, Sangeeta; Nurmatov, Ulugbek; Varga, Eva‐Maria; Sturm, Gunter; Muraro, Antonella; Akdis, Cezmi A.; Antolín‐Amérigo, Darío; Bilò, M. Beatrice; Bokanovic, Danijela; Calderon, Moises A.; Cichocka‐Jarosz, Ewa; Elberink, Joanna N. G. Oude; et al.
Abstract : Unfortunately this article [1] was published with an error in the Funding section. The BM4SIT project is not acknowledged. This section should be corrected to the below: Funding EAACI and the BM4SIT project (Grant Number 601763) in the European Union's Seventh Framework Programme FP7.